Respostas

2014-08-08T15:40:11-03:00
Use Equação de Baskara:

x = (- b ± √ b² - 4ac) / 2a

Nesse caso:

a = 4
b = 4
c = - 1

Então:

x = (- b ± √ b² - 4ac) / 2a
x = (- 4 ± √ (4)² - 4 . 4 . (- 1)) / 2 . 4
x = (- 4 ± √ 16 + 16) / 8
x = (- 4 ± √ 32) / 8
x = (- 4 ± 4 x √ 2) / 8

x' = (- 4 - 4 x √ 2) / 8
x' = (- 1 - √ 2) / 2

x''= (- 4 + 4 x √ 2) / 8
x''= (- 1 + √ 2) / 2

Você pode considerar (√ 2 = 1,41):

x' = (- 1 - √ 2) / 2
x' = (- 1 - 1,41) / 2
x' = (- 2,41) / 2
x' = - 1,205

x''= (- 1 + √ 2) / 2
x''= (- 1 + 1,41) / 2
x''= (0,41) / 2
x''= 0,205